Can inhaled cannabis users accurately evaluate impaired driving ability? A randomized controlled trial - Hartley, Sarah; Simon, Nicolas; Cardozo, Bibiana; Larabi, Islam Amine; Alvarez, Jean Claude (Frontiers in Public Health, 2023)
Aims To study the effect of inhaled cannabis on self-assessed predicted driving ability and its relation to reaction times and driving ability on a driving simulator. Participants and methods 30 healthy male volunteers aged 18–34: 15 chronic (1–2 joints /day) and 15 occasional (1–2 joints/week) consumers. Self-assessed driving confidence (visual analog scale), vigilance (Karolinska), reaction time (mean reciprocal reaction time mRRT, psychomotor vigilance test), driving ability (standard deviation of lane position SDLP on a York driving simulator) and blood concentrations of delta-9-tétrahydrocannabinol (THC) were measured before and repeatedly after controlled inhalation of placebo, 10 mg or 30 mg of THC mixed with tobacco in a cigarette. Results Cannabis consumption (at 10 and 30 mg) led to a marked decrease in driving confidence over the first 2 h which remained below baseline at 8 h. Driving confidence was related to THC dose and to THC concentrations in the effective compartment with a low concentration of 0.11 ng/ml for the EC50 and a rapid onset of action (T1/2 37 min). Driving ability and reaction times were reduced by cannabis consumption. Driving confidence was shown to be related to driving ability and reaction times in both chronic and occasional consumers. Conclusions Cannabis consumption leads to a rapid reduction in driving confidence which is related to reduced ability on a driving simulator. Clinical trial registration ClinicalTrials.gov, identifier: NCT02061020.